The Changing Global Context of Virtual Workforce - James A. Ejiwale (Intelektual Pustaka Media Utama, 2012)
The technological revolution occurring in today’s market place has made it possible for many companies to be innovative about the way and where work is done. To get the job done, due to digital revolution, companies have turned to virtual workforce to harness the benefits of connectivity and effective information sharing among stakeholders to get the job done. More important, the success of coordinating work among a virtual workforce for profitability in a rapidly changing global environment depends on “effective indirect communication” between the leadership and the virtual workforce. This article will address the importance of effective communication as a necessary tool for the success of e-leadership, productivity improvement in virtual work environment.